PRINCIPLES OF EXPANSION OF GENERAL MUSICAL THEORETICAL KNOWLEDGE OF MUSICIAN PERFORMERS (Spectrum Journal of Innovation, Reforms and Development, 2022)
This article describes practical performance skills in expanding musical theoretical knowledge in performance. The principles of expanding theoretical knowledge in executive practice are highlighted.